AN ANALYSIS OF THE STUDENTS’ PARAGRAPH COMPOSITIONPERFORMANCE - Samsul Amri; Boni Saputra (Politeknik Negeri Bengkalis, 2020)
An investigation ofcomposition performanceisimportant matter of contention toprobethat one may achievefurthercompelling and authenticending. Paragraph composition performance is one of the concerns.Thetarget of the contemporaryanalysisistoinspectthe extent to which the students’ paragraph composition performance. Therefore, survey study was conceived to achieve the purpose. The third semester students of English Study Program of FKIP – UNISI Tembilahan were determined as the shareholders. They were requiredto composetwo kinds ofparagraph; process paragraph and comparison/contrast paragraph. There are five evaluation criterions; format, punctuation and mechanics, contents, oganization, and sentence structure. Dealing the results ofdata analysis,itdisclosed that theirparagraph composition performance on each compositionelements was diverse. It could be justified from the datawhich sixparticipants (27.3%) worked outin the admirablegrade, nineof them (40.9%) were recognized in competent level, and sevenparticipants (31.8%) could achieve in sufficientcategory. As the final comment, it could be determined that their paragraph compositionperformance was in the sufficient to admirable level. Nevertheless, to gain better endings, more practice isbrought to their mind.